(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2021)
This study analyzed the impact give by extrinsic motivation and self-efficacy on academic stress on students at Jakarta State University. A quantitative methodology is the technique used in this study with the main model of multiple linear regression. Participants in this study were 159 students from various study programs at the Jakarta State University. The sampling technique was a simple random sampling technique. The data was collected by using a closed questionnaire using a Likert scale and applied using the google form application. Statistical calculations were carried out using SPSS 25, and the hypothesis test used the t-test and f-test. It was revealed that 1) Extrinsic motivation has a negative and significant effect on student academic stress, 2) Self-efficacy has a negative and significant effect on student academic stress and, 3) Extrinsic motivation and self-efficacy affect student academic stress by 88.6%.